ALTERNATIF STRATEGI PENGEMBANGAN USAHA PETERNAKAN SAPI PERAH DI KABUPATEN BOYOLALI BERBASIS ANALISIS SWOT - Hidayah, N. Hidayah; Guntoro, B. Guntoro; Sulastri, E. Sulastri (Jurnal Pengembangan Penyuluhan Pertanian, 2018)
This study aimed to analyze the strengths, weaknesses, opportunities and threats found in a study to determine the location of an alternative development strategy dairy cattle business in Boyolali. This research was conducted in three dairy cooperatives that Mojosongo Cooperatives, Musuk Cooperatives, and Cepogo Cooperatives using survey methods. Total survey respondents determination of alternative business development strategy of dairy cows in Boyolali many as 356 people. The analysis showed that the alternative strartegi that could be pursued include: maintaining and improving the quality of the partnership with the Village Unit Cooperatives and Milk Processing Industry, increasing the use of technology Artificial insemination to improve the reproductive rate so that the expected milk production can be increased and the demand for milk in the country can be met, and improving the performance of breeders of childbearing age in order to increase the productivity of dairy cattle for milk consumption fulfillment.Keywords: Dairy cows, Strategy, Cooperatives